LIBRA AS A DIGITAL CURRENCY AND ITS IMPACTS ON THE THAI ECONOMY - Limsakul, Anun; Kraiwanit, Tanpat (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
This qualitative research aims to study the acceptance of Libra and its impacts on the financial industry. Ten financial experts were interviewed. The questions used to measure expert opinion can be categorized into three groups: benefit, risk, and impact. The index of item-objective congruence was then used for content validation and Cronbach’s alpha was used for a reliability test. The findings show that experts are concerned about whether Libra can be used to purchase goods and services like other real currencies at a high-level agreement, while they have less worry about personal information leaks and Libra being a channel for money laundering and financial crimes. Moreover, the experts are unsure whether Libra can increase access to financial transactions among people who have limitations cannot access the branch of the bank, leading to a decrease in inequality. Financial experts consider that financial institutions will lose income from money transfer and service fees; however, deposit and loan services might not be affected. Moreover, experts’ opinions show that financial institutions need to offer quicker and user-friendly services via smartphone applications, should adjust the interest rate and service fees in accordance with the Libra system, and make joint investments with Libra. The study suggests that public sectors can create legislation and amend laws to be able to deal with digital currency: hence the problems caused by Libra will be minimized. In addition, financial institutions need to develop a mobile banking system, and services, interest rates, and service fees need to be taken into account.